Benfotiamine upregulates antioxidative system in activated BV-2 microglia cells - Bozic, Iva; Savic, Danijela; Stevanovic, Ivana; Pekovic, Sanja; Nedeljkovic, Nadezda; Lavrnja, Irena (Frontiers in Cellular Neuroscience, 2015)
Chronic microglial activation and resulting sustained neuroinflammatory reaction are generally associated with neurodegeneration. Activated microglia acquires proinflammatory cellular profile that generates oxidative burst. Their persistent activation exacerbates inflammation, which damages healthy neurons via cytotoxic mediators, such as superoxide radical anion and nitric oxide. In our recent study, we have shown that benfotiamine (S-benzoylthiamine O-monophosphate) possesses anti-inflammatory effects. Here, the effects of benfotiamine on the pro-oxidative component of activity of LPS-stimulated BV-2 cells were investigated. The activation of microglia was accompanied by upregulation of intracellular antioxidative defense, which was further promoted in the presence of benfotiamine. Namely, activated microglia exposed to non-cytotoxic doses of benfotiamine showed increased levels and activities of hydrogen peroxide- and superoxide-removing enzymes – catalase and glutathione system, and superoxide dismutase. In addition, benfotiamine showed the capacity to directly scavenge superoxide radical anion. As a consequence, benfotiamine suppressed the activation of microglia and provoked a decrease in NO and •O2- production and lipid peroxidation. In conclusion, benfotiamine might silence pro-oxidative activity of microglia to alleviate/prevent oxidative damage of neighboring CNS cells.